2016
DOI: 10.1007/s12032-016-0872-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of epithelial cell transforming sequence 2 predicts poor prognosis for prostate cancer

Abstract: Epithelial cell transforming sequence 2 (Ect2) was originally reported as an oncogene that is involved in several types of human cancers. However, little is known about its expression and function in prostate cancer. Immunohistochemical staining for Ect2 was performed on a human tissue microarray. The staining intensity was analyzed in association with clinical pathological parameters such as Gleason score, pathological grade, clinical stage, tumor invasion, lymph node and distant metastasis. Furthermore, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…ECT2 was highly expressed in prostate cancer, but it was slightly or not expressed in normal prostate tissue, and the difference was statistically significant. Overexpression of ECT2 was closely correlated with the clinical stage, tumour invasion and lymph node metastasis of prostate cancer, and survival analysis showed that it was an independent prognostic index in patients with prostate cancer 9. In gastrointestinal tumours, such as gastric cancer, colorectal cancer and esophageal cancer, ECT2 was highly expressed and the high expression of ECT2 was an effective marker as well as an important prognostic factor for poor prognosis 3 7 10.…”
Section: Discussionmentioning
confidence: 99%
“…ECT2 was highly expressed in prostate cancer, but it was slightly or not expressed in normal prostate tissue, and the difference was statistically significant. Overexpression of ECT2 was closely correlated with the clinical stage, tumour invasion and lymph node metastasis of prostate cancer, and survival analysis showed that it was an independent prognostic index in patients with prostate cancer 9. In gastrointestinal tumours, such as gastric cancer, colorectal cancer and esophageal cancer, ECT2 was highly expressed and the high expression of ECT2 was an effective marker as well as an important prognostic factor for poor prognosis 3 7 10.…”
Section: Discussionmentioning
confidence: 99%
“…High protein expression of ECT2 was reported in prostate cancer [13], lung cancer [14], colorectal cancer [15], and gastric cancer [16]. Mislocalization of ECT2 was found in ovarian cancer [17], osteosarcoma [12], and cervical cancer cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…Cytoplasmic staining was considered indicative of a positive signal on the basis of the antibody specification sheet. The staining intensity and percentage were used for semi-quantitative scoring of the expression intensity in each case, as described by a previous study (20). The staining intensity was scored as follows: Negative, weak, moderate and strong staining were scored as 0, 1, 2 and 3 points, respectively.…”
Section: Methodsmentioning
confidence: 99%